Anti-theft bicycle lock system / Nur Fitri Arif Nur Faridh - Nur Faridh, Nur Fitri Arif (2024)
This project introduces an Arduino-based anti-theft bicycle lock system, utilizing an Arduino Uno microcontroller in conjunction with a keypad, LED indicators, a buzzer, and an LCD display. The system enhances bicycle security by requiring user authentication through a keypad, with the LCD display providing real-time feedback on system status. To deter theft, the system features a bright LED indicator and a loud buzzer, serving as visual and audible deterrents. The Arduino Uno controls the locking mechanism, engaging a physical lock only upon successful authentication. Anti-tamper features trigger the alarm and notify the owner in case of unauthorized manipulation. The user-friendly design, combining visual and audible deterrents, offers an effective and customizable solution to enhance bicycle security, while the Arduino platform allows for scalability and future enhancements